A man's place : masculinity and the middle-class home in Victorian England - Tosh, John (Yale University Press, 1999)
"John Tosh shows how profoundly men's lives were conditioned by the Victorian ideal, and how they negotiated its many contradictions." "Tosh begins by looking at the experience of boyhood, married life, sex and fatherhood in the early decades of the nineteenth century - illustrated by case-studies representing a variety of backgrounds - and then contrasts this with the lives of the late Victorian generation. By the 1870s, men were becoming less enchanted with the pleasures of home. Once the rights of wives were extended by law and society, marriage seemed less attractive, and the bachelor world of clubland flourished as never before." "The Victorians declared that to be fully human and fully masculine, men must be active participants in domestic life. In exposing the contradictions in this ideal, they defined the climate for gender politics in the next century."--Jacket